DNA Methylation Patterns of Glucocorticoid Pathway Genes in Preterm Birth Among Black Women. Issue 4 (October 2022) - Nowak, Alexandra L.; Anderson, Cindy M.; Ford, Jodi L.; Mackos, Amy; Ohm, Joyce; Saadat, Nadia; Tan, Alai; Zhao, Yihong; Misra, Dawn P.; Giurgescu, Carmen
Preterm birth (PTB; <37 weeks gestation) rates have increased for 5 of the last 6 consecutive years in the United States. These rates are particularly alarming for U.S. non-Hispanic Black women who give birth prematurely at 1.5 times the rate of non-Hispanic White women. Previous research suggests that psychological stress is associated with PTB in Black women. However, the biological pathways by which stress alters birth timing are not clear. We examined DNA methylation (DNAm) in peripheral blood leukocytes in 6 glucocorticoid, stress-related genes in 44 (22 PTB; 22 term birth) pregnant Black women. Four cytosine-phosphate-guanine (CpG) sites were identified as differentially methylated ( p < 0.05) between women with PTB and women with term births. The ability to identify stress-related biological markers that are associated with PTB among Black women would provide a critical step toward decreasing the PTB disparity among these women. Future studies should include larger sample sizes and gene expression analyses of the stress-related biological pathways to PTB.